The impact of intrinsic and extrinsic factors on the safety and quality of hard and semi-soft natural cheese - Beard, Martin Gale (Kansas State University, 2009)
This paper reviews the safe production of hard and semi-soft natural cheeses made from pasteurized milk, starter cultures, and enzymatic coagulation. Historically, raw milk has been a source of pathogenic bacteria; however, High Temperature Short Time (HTST) pasteurization has been proven to effectively control these pathogens. The US Public Health Service (USPHS) and US Food and Drug Administration (FDA) promulgate the legal operational parameters in the Pasteurized Milk Ordinance (PMO) and Code of Federal Regulations (CFR) to ensure milk is properly pasteurized and that dairy products are made in accordance with these regulatory standards. A combination of factors in the production of these natural cheeses further inhibits microorganisms. Intrinsic factors include pH, oxidation-reduction potential, water activity, nutrient content, natural inhibitors, and physical integrity. Extrinsic factors include temperature, relative humidity, gaseous environment, cumulative stress, and storage time. These factors contribute to a multiple hurdle effect that inhibits pathogens and spoilage organisms while also providing operational parameters to ensure flavor, texture, and other quality targets. Hard and semi-soft natural cheeses have been associated with few cases of food borne illness over the last few decades. Nevertheless, many operations in the dairy industry have voluntarily implemented food safety systems such as HACCP to ensure the continuous safe production of hard and semi-soft natural cheese.
Keywords: dairy; cheese; quality; microbiology; chemistry; protein; Agriculture, Food Science and Technology (0359)